A collection of letters from South Australian settlers - Watson, Henry; Hack, John Barton, 1805-1884.; Hack, Bridget; Hack, Stephen; Watson, Charlotte; Darton, Thomas Gates (London Australian High Commission, 1900)
17 letters from John Barton Hack and Bridget, his wife, 1837-1944. 16 letters from Stephen Hack, 1837-1842. 23 letters from Henry Watson, and Charlotte, his wife, 1838-1843. 1 letter from Thomas Gates Darton quoting letters from John Hack and his wife Bridget, 1838.
Case has title: Hack family letters, 1837-1844
Microfilm copy of original documents in private ownership.
Keywords: Hack family -- Correspondence; Immigrants -- South Australia -- Correspondence